Ruthenium-Catalyzed Synthesis of Pyrrolo[1,2-a]quinoxaline Derivatives from 1-(2-Aminophenyl)pyrroles and Sulfoxonium Ylides - Cui, Xin-Feng; Hu, Fang-Peng; Zhou, Xiao-Qiang; Zhan, Zhen-Zhen; Huang, Guo-Sheng (Synlett, 2020)
A ruthenium-catalyzed [5+1] annulation of 1-(2-aminophenyl)pyrroles with α-carbonyl sulfoxonium ylides is reported. This reaction provides a one-step method for synthesizing pyrrolo[1,2-a]quinoxaline derivatives under ambient conditions. The system proceeds with a short reaction time and a high functional-group tolerance. Notably, this divergent protocol tolerates β-keto sulfoxonium ylides and can be applied to α-ester sulfoxonium ylides. A preliminary study was made of the mechanism of the reaction, and a reaction pathway is proposed.
Keywords: pyrroloquinoxalines; sulfoxonium ylides; aminophenylpyrroles; ruthenium catalysis; activation–cyclization; [5+1] annulation